2000
DOI: 10.1007/s001250051332
|View full text |Cite
|
Sign up to set email alerts
|

Response of Charcot's arthropathy to contact casting: assessment by quantitative techniques

Abstract: The assessment and management of Charcot's arthropathy has been limited by the lack of sensitive and objective assessment methods with clinical observation and radiography forming the mainstays of evaluation [1±7]. As a result, although rest and contact casting are accepted methods of treatment there is little objective data on their impact on the disease.Radionuclide scanning has been used to compare the affected foot of patients with or without Charcot's arthropathy [8]. We used two different methods of quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 6 publications
4
77
0
4
Order By: Relevance
“…In the present study we found that foot temperatures dropped significantly in the active and placebo groups as early as two weeks after entering into the study. The reduction in temperature in the placebo group is most likely due to the fact that all patients received off-loading measures in agreement with the observations of investigators that following total contact casting significant reduction in skin temperature was observed as well as reduction in bone isotope uptake [17]. In addition to the initial fall in temperature, we also found a further decrease in foot temperatures in the active group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study we found that foot temperatures dropped significantly in the active and placebo groups as early as two weeks after entering into the study. The reduction in temperature in the placebo group is most likely due to the fact that all patients received off-loading measures in agreement with the observations of investigators that following total contact casting significant reduction in skin temperature was observed as well as reduction in bone isotope uptake [17]. In addition to the initial fall in temperature, we also found a further decrease in foot temperatures in the active group.…”
Section: Discussionsupporting
confidence: 91%
“…Measuring foot temperatures has been shown to be an effective means of assessing activity of the Charcot foot [6]. In a recent study of acute CNA, skin temperature was shown to correlate with bone uptake of radio-isotope and disease activity [17]. In the present study we found that foot temperatures dropped significantly in the active and placebo groups as early as two weeks after entering into the study.…”
Section: Discussionsupporting
confidence: 58%
“…11 The intervention most often prescribed to assist in healing the foot is cast immobilization without weight bearing for 12 weeks. 3,12 This intervention, although effective in resolving the acute inflammation, may result in additional bone loss through disuse. 13 The purpose of this case report is to describe serial measures of BMD of the calcaneus, skin temperature, and edema in a patient with DM, acute neuropathic arthropathy, and renal failure (which required dialysis) during cast immobilization to resolve the inflammatory phase of the arthropathy.…”
mentioning
confidence: 99%
“…In a short communication, Mc Gill et al reported that bone uptake scintigraphy and skin temperature improved over 12 months with immobilization (McGill et al, 2000), but there are no studies evaluating changes in neither MRI nor bone scintigraphy after bisphosphonate treatment.…”
Section: Imaging and Biochemical Markers Of Bone Turnover After Medicmentioning
confidence: 99%